Gender and Economic Growth in Uganda : Unleashing the Power of Women - Ellis, Amanda; Manuel, Claire; Blackden, C. Mark (Washington, DC: World Bank, 2012)
Uganda is a leader in Sub-Saharan Africa, in recognizing linkages between economic growth and gender issues. These linkages are critical for achieving the Millennium Development Goals. The study assesses the legal and administrative barriers faced by women, as identified by the Bank's Foreign Investment Advisory Service (FIAS) and the International Finance Corporation's (IFC) Gender-Entrepreneurship-Markets Unit. The structure of the report mirrors that of the FIAS 2003 Administrative Barriers to Investment Report, and is designed to highlight the gender dimensions of that research to encourage further replication. The findings of this report indicate the considerable potential for economic growth that exists, if Uganda is to unleash the power of women, and support their full economic participation in the private sector. This assessment considers the relationship between gender and economic growth in Uganda in the context of promoting women's participation in business and entrepreneurship. Men and women both play substantial, albeit different, economic roles in the Ugandan economy. Each contributes about 50 percent of GDP, and women represent 39 percent of businesses with registered premises.